Synthesis and structural characterisation of the aggregates of benzo-1, 2-chalcogenazole 2-oxides. Issue 20 (21st April 2017) - Ho, Peter C.; Rafique, Jamal; Lee, Jiwon; Lee, Lucia M.; Jenkins, Hilary A.; Britten, James F.; Braga, Antonio L.; Vargas-Baca, Ignacio
Abstract : A benzoannulated iso-tellurazole N -oxide retains the ability to assemble supramolecular macrocycles. The selenium analogue crystallizes in supramolecular polymeric chains instead. Abstract : Iodine oxidation of bis[2-(hydroxyiminomethyl)phenyl] dichalcogenides yields benzo-1, 2-chalcogenazole 2-oxides. Annulated derivatives of iso-tellurazole N -oxides spontaneously aggregate into cyclic tetra- and hexamers through Te⋯O chalcogen bonding; the structures of the co-crystals with benzene and CH2 Cl2 illustrate the ability of these macrocycles to interact with small guest molecules. The selenium congener crystallizes forming a supramolecular polymer. VT NMR indicates that both compounds aggregate in solution but only at low temperature in the selenium case. The different abilities of these molecules to engage in supramolecular interactions are interpreted on the basis of their electronic properties evaluated with DFT-D3 calculations.